DiDi Couture / Nur Khairunnisa Roslan ... [et al.] - Roslan, Nur Khairunnisa; Asmayadi, Nor Farah Aizat; Zulkafli, Muhammad Danial; Zulkifli, Muhammad Ihsan; Zulkifli, Muhammad Izzudin (2021)
This business plan will introduce about DiDi Couture short, and long-term plan in the market. First of all, couture is base fashion design but more to custom made tailoring. It is commonly known with exclusive design with high-end top-quality fabric. Some of the couture provides high quality of fabric but charge the fees higher but our business offers a reasonable price for the customers since our business is new to in the market. We want to make sure that the customer recognizes our brand is far superior from the others competitor. Our concept of market segments targeting teenager and adults who wages around RM 5,000 and above. It is most likely a reasonable target market since the business wear is for someone working in the office. Demographic studies indicate that the economic in Kuala Lumpur would support our business because of the business economic rising in the market area. A large population of people who work in the company will surely need the business wear for their works attire. The operation of our business surely going smooth as it plans. With the amount of the worker and the unit production estimated for a day, DiDi Couture sure will see its vision in long-short term. The operation is well planning and organized to its detail. We want to ensure that the quality of the business wear Tuxedo satisfy the customer. customer’s feedback is important to maintain our position in the market target. If the feedback positive, our goal and objective can be achieved meanwhile if negative our share in target market will decrease drastically. In short, the business plan DiDi Couture is a plan that develop to ensure the business ongoing in the market segments and also to ensure that the business achieve the vision, mission, and objective of its company.